Laboratory Mice Are Frequently Colonized with Staphylococcus aureus and Mount a Systemic Immune Response—Note of Caution for In vivo Infection Experiments - Schulz, Daniel; Grumann, Dorothee; Trübe, Patricia; Pritchett-Corning, Kathleen; Johnson, Sarah; Reppschläger, Kevin; Gumz, Janine; Sundaramoorthy, Nandakumar; Michalik, Stephan; Berg, Sabine; van den Brandt, Jens; Fister, Richard; et al. (Frontiers in Cellular and Infection Microbiology, 2017)
Whether mice are an appropriate model for S. aureus infection and vaccination studies is a matter of debate, because they are not considered as natural hosts of S. aureus. We previously identified a mouse-adapted S. aureus strain, which caused infections in laboratory mice. This raised the question whether laboratory mice are commonly colonized with S. aureus and whether this might impact on infection experiments. Publicly available health reports from commercial vendors revealed that S. aureus colonization is rather frequent, with rates as high as 21% among specific-pathogen-free mice. In animal facilities, S. aureus was readily transmitted from parents to offspring, which became persistently colonized. Among 99 murine S. aureus isolates from Charles River Laboratories half belonged to the lineage CC88 (54.5%), followed by CC15, CC5, CC188, and CC8. A comparison of human and murine S. aureus isolates revealed features of host adaptation. In detail, murine strains lacked hlb-converting phages and superantigen-encoding mobile genetic elements, and were frequently ampicillin-sensitive. Moreover, murine CC88 isolates coagulated mouse plasma faster than human CC88 isolates. Importantly, S. aureus colonization clearly primed the murine immune system, inducing a systemic IgG response specific for numerous S. aureus proteins, including several vaccine candidates. Phospholipase C emerged as a promising test antigen for monitoring S. aureus colonization in laboratory mice. In conclusion, laboratory mice are natural hosts of S. aureus and therefore, could provide better infection models than previously assumed. Pre-exposure to the bacteria is a possible confounder in S. aureus infection and vaccination studies and should be monitored.